Addressing student plagiarism from the library learning commons. Issue 3 (12th March 2018) - Bell, Stephanie
Abstract : Purpose: The purpose of this paper is to conceptualize principled plagiarism education in library learning commons. Design/methodology/approach: The synthesis of literature from library and information science, writing studies, and study skills illuminates academic cultures of speech reporting, causes of undergraduate student cheating behaviors and blunders in source use and attribution, and recommended best teaching practices. Findings: Library learning commons are particularly well positioned to address student plagiarism as student-centric spaces with the potential to foster prosocial behaviors among students. Learning commons' partner literatures reveal understandings of academic citation practices as multiple and fluid, tacit, ideological and skillful information literacies. Best practices for plagiarism education are developmental approaches aimed at socializing students into academic cultures of knowledge construction. These approaches to plagiarism education may preclude teaching academic integrity policy or participating in the enforcement of those codes of conduct. Research limitations/implications: No survey of programs or their effectiveness was done for this paper. The effectiveness of the approach conceptualized here merits further study. Originality/value: Contributions to fostering academic integrity support student success and the integrity of degrees and institutional reputation more broadly. This paper provides a model for interdisciplinary learning commons' research.